2018
DOI: 10.1038/s41467-018-06189-y
|View full text |Cite
|
Sign up to set email alerts
|

Preventing acute asthmatic symptoms by targeting a neuronal mechanism involving carotid body lysophosphatidic acid receptors

Abstract: Asthma accounts for 380,000 deaths a year. Carotid body denervation has been shown to have a profound effect on airway hyper-responsiveness in animal models but a mechanistic explanation is lacking. Here we demonstrate, using a rat model of asthma (OVA-sensitized), that carotid body activation during airborne allergic provocation is caused by systemic release of lysophosphatidic acid (LPA). Carotid body activation by LPA involves TRPV1 and LPA-specific receptors, and induces parasympathetic (vagal) activity. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(85 citation statements)
references
References 68 publications
4
81
0
Order By: Relevance
“…Consistent with an essential role for parasympathetic innervation in asthma, we and others have shown that cervical vagotomy drastically suppresses acute asthmatic bronchoconstriction (Kesler & Canning, 1999;Wagner & Jacoby, 1999;Liu et al 2014;McAlexander et al 2015;Jendzjowsky et al 2018). Indeed, parasympathetic nerve endings in the lung release ACh (Kleij & Bienenstock, 2005;Cyphert et al 2009;Mazzone & Undem, 2016), substance P (Hunter & Undem, 1999), calcitonin gene-related peptide (Assas et al 2014) and vasoactive intestinal peptide (Talbot et al 2015); and receptors for these neurotransmitters are found in multiple cell types in the lung, including airway epithelium (Mazzone & Undem, 2016), fibroblasts (Kahler et al 2001;Matthiesen et al 2006), macrophages (Ichikawa et al 1995;Koarai et al 2012), neutrophils (Renshaw et al 2009), eosinophils (Costello et al 1997), T-lymphocytes (Blum et al 1992;Tayebati et al 1999), innate lymphoid cells (Talbot et al 2015) and mast cells (Cyphert et al 2009).…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Consistent with an essential role for parasympathetic innervation in asthma, we and others have shown that cervical vagotomy drastically suppresses acute asthmatic bronchoconstriction (Kesler & Canning, 1999;Wagner & Jacoby, 1999;Liu et al 2014;McAlexander et al 2015;Jendzjowsky et al 2018). Indeed, parasympathetic nerve endings in the lung release ACh (Kleij & Bienenstock, 2005;Cyphert et al 2009;Mazzone & Undem, 2016), substance P (Hunter & Undem, 1999), calcitonin gene-related peptide (Assas et al 2014) and vasoactive intestinal peptide (Talbot et al 2015); and receptors for these neurotransmitters are found in multiple cell types in the lung, including airway epithelium (Mazzone & Undem, 2016), fibroblasts (Kahler et al 2001;Matthiesen et al 2006), macrophages (Ichikawa et al 1995;Koarai et al 2012), neutrophils (Renshaw et al 2009), eosinophils (Costello et al 1997), T-lymphocytes (Blum et al 1992;Tayebati et al 1999), innate lymphoid cells (Talbot et al 2015) and mast cells (Cyphert et al 2009).…”
Section: Introductionsupporting
confidence: 77%
“…Thus, the parasympathetic nervous system has both direct and indirect means of activating (and inactivating) airway smooth muscle and has potentially powerful influences over the cytokine cascades involved in other aspects of AHR (Mazzone & Undem, 2016). Although evidence suggests that the lung surveys its environment (Belvisi, 2002;Undem & Potenzieri, 2012), it appears then that immune responses to allergens are governed at least in part from outside the lung (Nadel & Widdicombe, 1962;Jordan, 2001;Mazzone & Canning, 2002;Habre et al 2010;Fernández et al 2011;Nardocci et al 2015;Jendzjowsky et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models, LPA was found to trigger acute allergen and bradykinin-mediated bronchoconstriction by activating carotid body TRPV1 and LPA receptors, causing acute asthma symptoms. It was worth noting that this mechanism has not yet been confirmed in the human body, which can be used as a new research direction [149]. In a previous study, a mouse model of allergic asthma with LPA2 deficiency was found to be more severe than wild-type mice with pulmonary and systemic inflammation [150].…”
Section: Lpar and Asthmamentioning
confidence: 99%
“…Besides LPS and DAMPs, also the growth factor-like lipid lysophosphatidic acid (LPA) is worth being mentioned among potential modulators of the CB in inflammatory conditions. In particular, preclinical studies on a rat model of asthma showed that the administration of LPA, at concentrations present in the blood following allergen/bradykinin challenge, stimulate the CB by activating G-protein coupled receptors (GPCRs), causing acute bronchoconstriction [ 81 ]. Moreover, this effect is counteracted by blocking this pathway with receptor antagonists.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%